Advisory Committee on Immunization Practices recommended immunization schedule for adults aged 19 years or older — United States, 2019. Issue 4 (25th March 2019) - Kim, David K.; Hunter, Paul
Abstract : This report updates the immunization practices for adults 19 years old and older.